Research on 5G network base station site selection based on fruit fly optimization algorithm - Wei HUANG (Dianxin kexue)
Faced with the fact that the spatial distribution of buildings is not considered in the location of 5G network base stations, which makes the base station site selection effect unsatisfactory and leads to the problem of small coverage of base stations, a research method for 5G network base station site selection based on fruit fly optimization algorithm was proposed.The distance from the front line base station to the circular coverage center was calculated, and the satellite communication equipment was used to locate the return signal to obtain the optional position area of the rear base station.The energy consumption of data reception, transmission and aggregation were calculated, and the load balancing of base station data was ensured under the premise of balanced distribution of cellular units.A two-layer location model for base station site selection was built, constraints were set, and the optimal location of base station was determined.The fruit fly optimization algorithm was used to update the position, and after individual update iterative processing, it was not to fall into local optimization and obtain the fine base station site selection position.It can be seen from the experimental results that the minimum losses of the front line and rear base stations in this method are 50 dB and 70 dB, respectively, and the coverage radius of the base station is 6 km, which is consistent with the coverage of the ideal base station.